Plasterwork in the Ambassadors Hall (Salón de Embajadores) of the Real Alcázar of Seville (Spain): Graphic reconstruction of polychrome work by layer characterization. (15th March 2016) - Blasco-López, F.J.; Alejandre, F.J.; Flores-Alés, V.; Cortés, I.
Highlights: Stratigraphic studies supplied data on polychromy changes in plasterwork. Plasterwork polychromies structure have been characterized to define their evolution. Graphic analysis and 3D modeling are used for reconstruction from its original state. Abstract: This work examines a polychrome plasterwork in one of the most important scalloped arches in the Ambassadors Hall (Salón de Embajadores), which is the most outstanding room in the Mudéjar Palace of the Real Alcázar of Seville (Spain). Characterization by stratigraphy, XFR, XRD, and FTIR studies has supplied data on changes in the composition and colors in this building element. The research is complemented with historical information on the most significant interventions in this hall. Graphic analysis and the modeling of decorative geometric elements in 3D with BIM software were used to simulate its evolution from its original state. The results characterize the base plasterwork and the polychromies constituted by 1–3 microlayers with a thickness between 5 and 300 μm, formed of blue (19.88% Cu-azurite), vermilion (19.00% Pb-massicot and 5.34% Hg-cinnabar), and golden layers (68.93% Au). The colors were obtained through the use of mineral pigments such as azurite, cinnabar-litharge, and gold-leaf, respectively. The rich colors visible in this hall now have varied over time.